Fungal and viral oral infections in individuals with onco-hematologic neoplasms in a University Hospital - Thaiane Dantas Dias dos Santos; Patrícia Miranda Leite Ribeiro; Renata Portela de Rezende; Davi Silva Carvalho Curi; João Frank Carvalho Dantas de Oliveira; Viviane Almeida Sarmento (Universidade Estadual de Campinas, 2017)
Introduction: Individuals undergoing onco-hematologic treatment present higher risk for developing oral and/or systemic infections, due to the intense immunosuppression and compromise of the mucosal barriers during treatment. The aim of this study was to identify the fungal and viral oral infections that most frequently affected patients undergoing onco-hematologic treatment in a University Hospital, and relate them to the biopsychosocial data, underlying disease and treatment. Methods: This was a crosssectional study in which descriptive analysis of the data was performed, and the Exact Fisher test was applied to verify the association between the infections and the variables: sex, age group, educational level, underlying disease and treatment, considering a 5% probability of error. Results and Discussion: The clinical exam revealed that oral candidiasis was present in 8.92% of the individuals, and herpes simplex, in 4.5%. No significant associations were found between the variables and infections. The fungal and viral oral infections were little prevalente in individuals with hematologic neoplasms in the present study, suggesting that the action of dental surgeons in caring for the onco-hematologic patients at the Institution evaluated and the protocols use were efficient.